Pesticides organo-chlores dans les organismes de la Mer Noire - Șerbănescu, Octavian; Mihnea, Radu; Bilal, Icmet (Cercetări Marine - Recherches Marines, 2026)
The authors present the organochlorine pesticides content (α, β, γ) HCH, dieldrin, DDT, DDD and DDE determined in the muscle tissues of the eight fishes and two mollusk species, caught at the Romanian Black Sea coast, in the May-August 1978.